Evaluation of CD4+ T cells in HIV patients presenting with malaria at the University of Ilorin Teaching Hospital Nigeria - Agbede, Olajide O.; Ajiboye, Temitope O.; Babatunde, Samuel A.; Kolawole, Olatunji M.; Odeigha, Louis O. (Technische Universität Dortmund, 2010)
CD4 count is an important immunological marker of disease progression in HIV seropositive patients. This study was carried out to determine the effect of malaria or fever of unknown origin on the population of CD4+ T lymphocytes of HIV seropositive patients attending the highly active antiretroviral therapy (HAART) clinic of the University of Ilorin Teaching Hospital, Ilorin, Nigeria. 36 subjects were selected for this study. Ongoing history of fever was used as a case definition for malaria and malaria was confirmed from microscopic examination of thick and thin film of blood sample obtained from the patients during presentation with fever. The CD4 count was evaluated during presentation of fever and post-fever using flow cytometry. There was significant decrease in CD4 count of the patients. However, upon classifying the patients into 2 groups – those that returned to the clinic after a week and those that returned after a month; a significant increase in CD4 count was noticed in the group that returned after a week, while a significant decrease was noticed in the group that returned after a month (at p value of 95 %). Further classification of the patients based on presence of malaria parasite, and body temperature resulted in varying effects on CD4 count post-fever (in the general group, 27 were positive for malaria parasites). Of these 27, there was an increase in CD4 count in 9 (33.3 %). However in the group that returned after a week, all 6 (100 %) that were positive for malaria parasites showed increase in CD4 count. Five (26.3 %) of the 19 patients that had body temperature within the range of 35.5-37.4 °C showed an increase in CD4 count, while 7 (41.2 %) of the 17 patients that had body temperature of 37.5 °C and above showed an increase in CD4 count. The results led to the conclusion that while some components of the immune response to malaria could strengthen the immune system of HIV seropositive patients by increasing their CD4 count, other components will suppress their immunity by decreasing their CD4 count, accelerating the progression to AIDS.
EXCLI Journal ; Vol. 9, 2010
Keywords: CD4 Count; CD4+ T lymphocytes; Flow cytometry; HIV/AIDS; Immune system; Malaria; 610